Macroeconomic determinants of foreign aid inflows in North African countries - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2023)
This study examined the determinants of foreign aid inflows in North African countries using panel data (1989-2019) analysis. The study also explored the influence of the complementarity between trade openness and foreign direct investment on foreign aid inflows in North African countries using the same data set. Several gaps, divergent, mixed and conflicting views in the literature prompted the author to investigate this topic to contribute towards the discourse. Trade openness (fixed effects, fully modified ordinary least squares), the complementarity between trade openness and foreign direct investment (pooled ordinary least squares), personal remittances (dynamic ordinary least squares, pooled ordinary least squares), population growth (pooled ordinary least squares) and government consumption expenditure (fixed effects, fully modified ordinary least squares, pooled ordinary least squares) were found to have had a significant positive influence on foreign aid inflows into North African countries. Foreign direct investment (pooled ordinary least squares) and economic growth (fixed effects, fully modified ordinary least squares, pooled ordinary least squares)’s negative impact on foreign aid inflows into North African countries was found to be significant. To attract more foreign aid, North African countries are advised to implement trade openness, personal remittances inflow, population growth and government consumption expenditure enhancement policies. A study on threshold regression analysis of the determinants of foreign aid inflows in North African countries adds value in as far as erudite policy making is concerned.